Abnormal semen parameters among males in infertile couples: a cross sectional study from a tertiary care centre - Garg, Jyoti; Meena, Rachana; Shukla, Shailaja; Sharma, Sunita; Choudhury, Riva (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: In India, the prevalence of primary infertility ranges from 3.9% to 16.8%. Male factor contributes 40-50% of this. Male factor infertility is indicated by decreased sperm concentration, reduced motility, vitality or abnormal sperm morphology. Semen analysis is the single most important investigation to detect male factor infertility. The aim of this study was to analyse the prevalence of abnormal semen parameters among males in infertile couples and their association with contributing factors. Methods: This cross-sectional hospital-based study was carried out in the Department of Pathology at Lady Hardinge Medical College and Smt. Sucheta Kriplani Hospital. A total of 400 cases were analyzed during a period of 6 months. Detailed history of the couple was taken. Semen analysis was done using automated semen analyzer (SQA-vision) after 3 days of abstinence according to the WHO 5th edition 2010 guidelines. The results were analysed using excel sheet and SPSS software. Results: In the present study, 122 cases (30.5%) out of 400 cases had abnormal semen parameters. Most common abnormality detected was asthenozoospermia (14.3%) followed by oligozoospermia (13.8%), azoospermia (10.5%) and teratozoospermia (10.5%). There was significant association of alcohol intake, obesity and trauma with abnormal semen parameters. Conclusions: Asthenozoospermia was the most common abnormality noted in this study. Lifestyle modifications along with timely medical attention in male partners of infertile couples can improve the semen quality.